Gamification I en finansiell kontext - Bergquist,Edvin; Andersson,Ossian; Brodahl,Karl (2025)
The purpose of this study is to investigate the factors determining continuous user-engagement for the elements Avanza Svajper and Milstolpar. By analyzing qualitative insights from both users and Avanza representatives, and interpreting the findings through the lenses of Self-Determination Theory, the Octalysis Framework, and the MDA Framework, this study provides a deeper understanding of the strategic considerations behind the implementation of gamified elements and how game-inspired elements influence user-engagement and perception. The study shows that Avanza implemented these features to enhance user experience and support long-term saving. Milstolpar largely met this goal by visualizing progress and fostering motivation, although its effect could diminish when milestones felt distant. Avanza Svajper, launched without firm expectations, was perceived as intuitive and engaging, especially by less experienced investors. While some concerns emerged around impulsive decision-making, both features successfully activated psychological drivers such as curiosity, achievement, and progression. Overall, the findings highlight how game-inspired design can positively influence user engagement when applied thoughtfully within a financial context.
Keywords: Gamification; Engagemang; Användarupplevelse; Interaktionsdesign; Fintech; Motivation.